The Influence Of Product Quality And Price On Purchasing Decisions On Mother Of Pearl Products From Tasya Farasya (Case Study of Students Management of Indonesian Islamic University) - Anetta Marriel Santoso; Agus Abdurrahman (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to investigate the influence of product quality and price on purchase decisions for the "Mother of Pearl" products by Tasya Farasya . Within this framework, data were collected through surveys administered to consumers who have direct experience with the product. Data processing utilized linear regression analysis to evaluate the relationship between the variables under scrutiny. The research findings indicate that both product price and quality significantly affect consumer purchasing decisions. The implications of the study suggest the importance of continually improving the quality of Mother of Pearl products and offering prices that align with the quality of the products.